Beowulf by All Community Translation and Workbook - Abbott, Jean; treharne, elaine; Fafinski, Mateusz (Foundations, 2021)
Beowulf By All is the first ever community translation of the poem known as Beowulf, and is published here for the first time in workbook form as Beowulf By All: Community Translation and Workbook in order to provide space and an added incentive for readers to assemble their own working translations alongside this one.